Effect of electroacupuncture versus solifenacin for moderate and severe overactive bladder: a multi-centre, randomized controlled trial study protocol - Qian Wen; Ning Li; Xueling Wang; Hao Li; Fengwei Tian; Weiwei Chen; Yanyan Lu; Zhishun Liu (BMC, 2020)
Abstract Background Overactive bladder is defined as "urgency, with or without urge incontinence, usually with frequency and nocturia". Electroacupuncture may be a safe and an effective alternative therapy for overactive bladder, but the evidence is limited. Methods We will conduct a three-arm, non-inferiority, multi-centre randomized controlled clinical trial. A total of 420 patients with moderate and severe overactive bladder will be randomly assigned to one of three groups: the electroacupuncture group (N = 140), sham electroacupuncture group (N = 140), and solifenacin group (N = 140). The primary outcome will be the change in the overactive bladder symptom score from baseline to the end of the 12-week treatment. The secondary outcomes will include the proportion of participants with a decrease in the overactive bladder symptom score ≥ 3 at weeks 4, 8, 12, 20, and 32; the change in average 24 h values of urination, nocturnal urination, urgency incontinence and urgency episodes from baseline to weeks 4, 8, 12, 20 and 32, and so forth. The adverse events will be recorded. Statistical analysis will include covariance analysis, nonparametric tests and descriptive statistics. Discussion This study will answer the question of whether electroacupuncture is effective and non-inferior to solifenacin for improving the symptoms of overactive bladder patients. Trial registration Chinese clinical trial registry ( ChiCTR1800019928 ).